Comparative safety of vascular closure devices and manual closure among patients having percutaneous coronary intervention - Gurm, Hitinder S; Hosman, Carrie; Share, David; Moscucci, Mauro; Hansen, Ben B (Annals of internal medicine, 2013)
The role of vascular closure devices (VCDs) in patients having percutaneous coronary intervention (PCI) is controversial, and recommendations for use vary. To examine the use of and outcomes associated with VCDs in real-world practice. Observational cohort study. 32 hospitals in Michigan that participate in a large multicenter quality improvement collaborative. Consecutive patients having emergent and nonemergent PCI from 2007 to 2009. Vascular complications and the need for transfusion. Of the 85 048 PCIs performed during the study that met the inclusion criteria, 28 528 (37%) procedures used VCDs. In propensity score-matched analysis, VCDs were associated with reductions in vascular complications (odds ratio [OR], 0.78 [95% CI, 0.67 to 0.90]; P = 0.001) and postprocedure transfusions (OR, 0.85 [CI, 0.74 to 0.96]; P = 0.011). These findings were consistent across many prespecified subgroups except for patients with a body mass index (BMI) less than 25 kg/m2 and those treated with platelet glycoprotein (GP) IIb/IIIa inhibitors, in whom the benefit of VCDs over manual closure was attenuated. When the specific subtypes of vascular complications were evaluated, VCDs were associated with fewer hematomas (OR, 0.69 [CI, 0.58 to 0.83]; P < 0.001) or pseudoaneurysms (OR, 0.54 [CI, 0.38 to 0.76]; P < 0.001) but an increase in the odds of retroperitoneal bleeding (OR, 1.57 [CI, 1.12 to 2.20]; P = 0.009). Unmeasured confounding cannot be excluded despite the study having measured and balanced many confounders. Vascular closure devices were associated with a significant reduction in vascular complications and need for transfusion in this large cohort of patients having transfemoral PCI. This benefit was lost in patients receiving GP IIb/IIIa inhibitors and those with normal or lean BMI and was counterbalanced by a small increase in the more serious risk for retroperitoneal bleeding.